2016
DOI: 10.18632/oncotarget.13471
|View full text |Cite
|
Sign up to set email alerts
|

Is the positivity of estrogen receptor or progesterone receptor different between type 1 and type 2 endometrial cancer?

Abstract: Endometrial cancer is a major cancer in women and traditionally divided into type 1 and type 2. It is well known that type 2 endometrial cancer has a poor prognosis. Studies have suggested that estrogen receptor (ER) or progesterone receptor (PR) positive are positively associated with endometrial cancer survive. However whether the positivity of ER or PR is different between cancer types has not been investigated yet. In this retrospective study, the positivity of ER or PR was analysed in 1054 women with prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 26 publications
10
40
1
Order By: Relevance
“…Hormone receptor status is also correlated with the aforementioned clinicopathologic traits. Specifically, the loss of ER and PR status is associated with EC lesions that are designated as type II, of higher tumor grade, and are more prone to deep myometrial invasion [2,3,17,28,29,31]. In this study, the statistically significant difference in FIGO staging by immunohistochemistry (IHC) further lends support to the notion that a decrease in ER expression is correlated to more advanced stages of EC (p<0.05) ( Table 2).…”
Section: The Independent Association Of Er and Pr Receptor Status With supporting
confidence: 66%
See 3 more Smart Citations
“…Hormone receptor status is also correlated with the aforementioned clinicopathologic traits. Specifically, the loss of ER and PR status is associated with EC lesions that are designated as type II, of higher tumor grade, and are more prone to deep myometrial invasion [2,3,17,28,29,31]. In this study, the statistically significant difference in FIGO staging by immunohistochemistry (IHC) further lends support to the notion that a decrease in ER expression is correlated to more advanced stages of EC (p<0.05) ( Table 2).…”
Section: The Independent Association Of Er and Pr Receptor Status With supporting
confidence: 66%
“…Among them, the most recent figures by Tomica, Ramic [28] reported a positive rate of 65.2% for ER expression and 59.4% for PR expression in a Caucasian population. Interestingly, while our data on ER and PR receptor status resonates with those found in a Caucasian population, our positive rates are lower in comparison to those reported in a Chinese cohort by Shen et al [17], which showed an overall rate of 85% for both ER and PR expression. Such disparity may be the result of the sequential loss of receptors in disease progression [26], as patients were neither stratified by the year of diagnosis, nor was the duration of EC analyzed in either study.…”
Section: Independent Er and Pr Receptor Status In Ecsupporting
confidence: 66%
See 2 more Smart Citations
“…Our objective in this study was to re-evaluate select molecular markers of purported prognostic significance: L1-cell adhesion molecule (L1CAM) [14][15][16], progesterone receptor (PR) [17][18][19], estrogen receptor alpha (ER) [18][19][20], stathmin (STMN) [21,22], and phosphatase and tensin homolog (PTEN) [23,24], assessing their value in the framework of modern molecular classification (by ProMisE).…”
Section: Introductionmentioning
confidence: 99%